Perceiving to learn or learning to perceive? Understanding farmers' perceptions and adaptation to climate uncertainties. (March 2016) - Nguyen, Thi Phuoc Lai; Seddaiu, Giovanna; Virdis, Salvatore Gonario Pasquale; Tidore, Camillo; Pasqui, Massimiliano; Roggero, Pier Paolo
Abstract: Perception not only shapes knowledge but knowledge also shapes perception. Humans adapt to the natural world through a process of learning in which they interpret their sensory impressions in order to give meaning to their environment and act accordingly. In this research, we examined how farmers' decision making is shaped in the context of changing climate. Using empirical data (face-to-face semi-structured interviews and questionnaires) on four Mediterranean farming systems from a case study located in Oristano (Sardinia, Italy) we sought to understand farmers' perception of climate change and their behaviors in adjustment of farming practices. We found different perceptions among farmer groups were mainly associated with the different socio-cultural and institutional settings and perceived relationships between climate factors and impacts on each farming systems. The research findings on different perceptions among farmer groups can help to understand farmers' current choices and attitudes of adaptation for supporting the development of appropriate adaptation strategies. In addition, the knowledge of socio-cultural and economic factors that lead to biases in climate perceptions can help to integrate climate communication into adaptation research for making sense of climate impacts and responses at farm level. Highlights: Farmers perceive more weather variability rather than to climate change. Different perceptions are due to different climate impacts on farming system. Farmers' adaptation emerges from perceiving processes. Adaptive capacity is driven by social capital, institutional setting and technology. "Learning to perceive" is essential for enhance farmers' adaptation to climate change.